Tunicamycin‐induced neutrophil extracellular trap (NET)‐like structures in cultured human myeloid cell lines. (19th November 2014) - Nakayama, Tomofumi; Saitoh, Hisato
Abstract: The mechanism of neutrophil extracellular trap cell death (NETosis), a regulated cell death pathway relevant to infection, autoimmunity and sepsis, is not completely known. The reason for this, at least in part, is the lack of an in vitro system that recapitulates the NETosis pathway using established human cell lines. We show that exposure of a human promyelocytic leukemia cell line HL‐60 to the glycosyltransferase inhibitor tunicamycin (TM) resulted in extrusion of decompacted genomic DNAs to extracellular space, morphologically similar to NETs. Immunostaining using antibodies against NET marker proteins and bacterial trapping assay showed biochemical similarities between the TM‐induced extracellular DNA structures and NETs. The NET‐like structures were also generated on exposure of TM to other myeloid cell lines, such as U937 and THP‐1. Thus, our findings provide an experimental setting to induce NET‐like structures using cultured human myeloid cell lines, which may help our understanding of the regulation and function of NETosis.